Expressive connotations in Saad Al-Basri's sculptures: سناء عبد الامير حسين القيسي (Al-Academy, 2021)
This research deals with an aesthetic discourse that depends on the expressive connotations and the aesthetics of its formation in sculpture, The sculptural works of the artist Saad Al-Basri were chosen as a model, Therefore, it deals with a contemporary plastic topic that benefits art education students and plastic arts students, The method of using materials and their formation methods has evolved and the great change that took place in the taste has developed, As the more knowledge and viewing of artworks increases in research and studies, it leads to an increase in aesthetic taste and aesthetic sense, which is reflected in the artistic achievements of students in the implementation of their work, A field study was conducted to view his sculptural products, which amounted to (30) completed, and (6) artistic products were selected from them as an intentional sample, The most important of them, The products had intentional expressive connotations that were executed with high precision, It included different periods and was implemented with various materials and for different topics, It was analyzed, A number of results and conclusions were reached, the most important of which were, The products have intentional expressive connotations that were implemented with high precision, which contributed to stimulating the feelings and feelings of the recipients and interacted with their ideas and aspirations, The sculptor used a variety of different materials in its completion, in addition to the use of color as one of the elements of expression, and all of them came as a result of specific events that the nation was exposed to and had a great impact on the achievement,